Hybrid napier grass* a boon to forage production - Bhakar, Ankur; Ram, Hardev (Indian Farming, 2019)
Napier grass or elephant grass (Pennisetum purpureum) is a widely distributed perennial grassgrown in tropical and subtropical regions of Asia, Africa, southern Europe and America. It isadaptable to wide range of agro ecological conditions and has vigorous vegetative growth, highbiomass production and deep rooted system to survive under adverse climatic conditions. Thehybrid napier grass can be maintained as a productive fodder crop for 3 to 4 years on same field.Whereas, the other forage crops are seasonal in nature and scarcity of fodder may occur during offseasons and also seasonal crops require repeated tillage operations for sowing which adds to the costof cultivation.